Current situation of Arabic language studies in Jordan universities - Abdul Jabar, Mohd Azidan; Al-Azzam, Zeyad Faisal (2015)
Hashemite Kingdom of Jordan is often considered one of the most popular educational hubs for Middle East and North Africa (MENA) region. Although the country is small in size and population, but it is big in its agenda to develop its higher education system. It has a substantial number of higher education institutions that offer various academic programmes. One of its most sought after programmes by foreign students especially from Malaysia are Arabic Language and Studies. The number of Malaysian students taking Arabic programmes in Jordan is increasing every year. On the same note, we find in Malaysian that many Arabic teachers and scholars are the graduates of universities in Jordan. They have been doing their role in developing Arabic language teaching and learning programmes and modules in educational institutions in Malaysia. This paper will look briefly at the overall situations of Arabic language programmes offered by public universities in Jordan and to show how our Malaysian institutions could benefit from Jordan experience in developing its national language in higher education institutions.